1998
DOI: 10.1074/jbc.273.31.19853
|View full text |Cite
|
Sign up to set email alerts
|

The Ah Receptor Is Not Involved in 2,3,7,8-Tetrachlorodibenzo-p-dioxin-mediated Apoptosis in Human Leukemic T Cell Lines

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a common environmental pollutant causing public concern.Its toxic effects include disruption of the immune, endocrine, and reproductive systems, impairment of fetal development, carcinogenicity, and lethality in rodents. Here, we report that TCDD induces apoptosis in two cultured human leukemic lymphoblastic T cell lines. This cell death was found not to be dependent on an aryl hydrocarbon receptor and to be inhibited by the inhibitor of tyrosine kinases and caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 45 publications
4
40
0
1
Order By: Relevance
“…A recent study by Tian et al (36) demonstrated physical interaction of the AHR with NF-B, leading to mutual repression in their system. Upon exposure to TCDD, c-jun, c-fos, and c-Jun N-terminal kinase induction has been observed in hepatoma cell lines (37,30) and in Jurkat cells (38). Thus, indirect up-regulation of IL-2 by TCDD via these factors is possible.…”
Section: Discussionmentioning
confidence: 92%
“…A recent study by Tian et al (36) demonstrated physical interaction of the AHR with NF-B, leading to mutual repression in their system. Upon exposure to TCDD, c-jun, c-fos, and c-Jun N-terminal kinase induction has been observed in hepatoma cell lines (37,30) and in Jurkat cells (38). Thus, indirect up-regulation of IL-2 by TCDD via these factors is possible.…”
Section: Discussionmentioning
confidence: 92%
“…Although AhR is a receptor for TCDD, AhR-independent effects of TCDD have also been reported (Hossain et al, 1998;Ahmed et al, 2005). Differentiated THP-1 macrophages were treated with α-naphthoflavone (α-NF), an AhR antagonist, together with TCDD.…”
Section: Ahr Mediates Up-regulation Of Tnf-α Expression By Tcddmentioning
confidence: 99%
“…In addition to its activity as a transcription factor, the ligand binding to AhR also triggers signal transduction pathways. However, this receptor-based model cannot explain all the biological effects of TCDD, and AhR-independent effects of TCDD have also been reported (Hossain et al, 1998;Ahmed et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppression, tumor promotion, and teratogenesis are well known toxic effects of these compounds in vertebrates (1)(2)(3)(4).…”
mentioning
confidence: 99%